When Does Capacity Development Achieve Good Outcomes? : Evidence from the IMF Results-Based Management Data - Bassanetti, Antonio (IMF Working Papers; Working Paper ;, 2021)
Capacity development is one of the IMF's core activities. Its impact is monitored through a Results-Based Management framework. Using for the first time the resulting dataset, the paper investigates how the likelihood of achieving targeted outcomes correlates with macroeconomic conditions and project-specific characteristics. Results indicate a positive correlation with per capita GDP growth and the involvement of resident advisors and regional centers. Results also confirm lower chances of achieving targeted outcomes for fragile, conflict-affected, and small states as well as in complex projects. These findings inform Fund CD strategy, prioritization and delivery to help member countries achieve better outcomes.